PENGEMBANGAN VIDEO ANIMASI MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV DALAM KURIKULUM MERDEKA DI SEKOLAH DASAR - Wiwik Okta Susilawati; M. Anggrayni; Riyan Nurcahyo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is motivated by the lack of interesting learning media available in schools and the teacher's not optimal use of technology. The desire of students to have interesting learning media that presents various images is also the background in this research. To overcome these problems, researchers are trying to develop an interesting learning media, namely animated videos for Pancasila educational subjects, especially in chapter IV of the subject matter of Negaraku Indonesia in the independent curriculum with the aim that teachers and students have adequate learning media and maximize the use of technology in the era of society. This. This type of research is Research and Development (R&D) with 5 stages namely Analyze, Design, Development, Implementation, Evaluate. The results obtained from the development of this animated video get a validator result of 90% and a practicality score with a result of 97.5%.